2022
DOI: 10.15611/fins.2022.2.05
|View full text |Cite
|
Sign up to set email alerts
|

Impact of FinTech on Sustainable Development

Abstract: Since the global financial crisis of 2008, we have observed a very rapid increase in use of digital technologies in the finance and development of FinTech companies, and similarly the impact of climate risk on banking. The aim of the paper was to examine the impact of FinTech on achieving sustainable climate and social goals through innovative financial instruments. FinTech can boost the development of green finance, which addresses environmental protection or climate change and has become an opportunity for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…It has the potential to reduce costs, facilitate global connectivity, and enhance financial inclusion. Recognizing its significance, the G20 and the UN have included "Sustainable digital finance" in their workstreams for 2030 (90)(91)(92)(93)(94). Awais et al (22) concluded that FinTech (measured by Internet popularization and Findex) have positive effects on green economic activity while carbon emissions have a negative impact.…”
Section: Fintech Financial Inclusion and Sustainable Development: Wha...mentioning
confidence: 99%
“…It has the potential to reduce costs, facilitate global connectivity, and enhance financial inclusion. Recognizing its significance, the G20 and the UN have included "Sustainable digital finance" in their workstreams for 2030 (90)(91)(92)(93)(94). Awais et al (22) concluded that FinTech (measured by Internet popularization and Findex) have positive effects on green economic activity while carbon emissions have a negative impact.…”
Section: Fintech Financial Inclusion and Sustainable Development: Wha...mentioning
confidence: 99%
“…The rise of fintech, an amalgamation of finance and technology, demonstrates the increasing utilization of digital SME loans, not limited to rural areas. Digital finance, particularly in the domain of digital payments, has notably transformed the landscape of financial service provision, showcasing remarkable effects (Mills, 2023;Pawłowska et al, 2022;Rowan, 2023).…”
Section: Technology-enhanced Financial Innovation In Rural Areasmentioning
confidence: 99%